Improving English Pronunciation Competence Using Imitation Technique in mmmenglish.com Website - Tugiyatun, Menuk; Ardini, Sukma Nur; Hawa, Faiza (Jurnal Bahasa Inggris, 2021)
The aims of this research are to investigate the effectiveness of the implementation of the imitation technique in mmmenglish.com website to improve students’ pronunciation and to find out students’ perception of using the media. This research employed a pre-experimental research design with the instruments, namely pre-test and post-test, questionnaire perception, and interview. The subject of this research was the eighth grade which consists of 15 students of SMP N 1 Pringapus, Semarang Regency. The results were shown by pre-test and post-test score categories. The pre-test scores indicated that there were 3 (20%) students in the excellent category, 1 (7%) student in the good category, 2 (13%) students in the fair category, 6 (40%) students in the poor category, and 3 (20%) students in the bad category. The post-test score indicated that there were 6 (40%) students in the excellent category, 5 (33%) good, 4 (27%) in the fair category, and none who were categorized bad. Therefore, the pronunciation abilities of the subjects improved after the treatment. It can be seen that the post-test scores of students were higher than the pre-test in the excellent category. The second result is about the students’ perception of using imitating techniques on the mmmenglish.com website. It can be seen that 42% of students were favored with a very high criterion, and 58% of the students were favored with a high criterion. The results showed that the student's responses to using imitation techniques on the mmmenglish.com website to improve their pronunciation ability were positive.